Development of A Problem-Based Learning Teaching Module In Differentiated Instruction to Improve Science Literacy of 4th Grade Students - Maria Kurniawati; Erny Roesminingsih; Maman Rumanta (CV. Edujavare Publishing, 2026)
Science learning in elementary schools often faces challenges related to low science literacy and limited accommodation of students’ diverse learning needs. These issues highlight the need for instructional designs that promote active learning while addressing individual differences. This study aims to develop and examine the effectiveness of a differentiated learning module based on the Problem-Based Learning (PBL) approach for teaching plant structure and function in elementary science education. The research employed a research and development method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The subjects included fourth-grade students and teachers from several elementary schools, with data collected through tests, questionnaires, observations, and interviews. Data analysis involved descriptive statistics, normality and homogeneity tests, paired samples t-tests, and N-gain analysis. The findings indicate that the developed module is valid, practical, and effective in supporting science learning. The implementation of differentiated PBL contributes to improved student engagement, conceptual understanding, problem-solving ability, and creative thinking in science learning contexts. The novelty of this study lies in the integration of differentiated instruction and PBL within a systematically designed elementary science module using the ADDIE framework. The study provides practical implications for teachers in designing inclusive science instruction and offers academic contributions to the development of innovative pedagogical models in elementary education.